(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article widely analyzes the improvement of technologies for developing critical thinking in future teachers through a competency-based approach. It discusses the essence of critical thinking, teaching strategies, reflective practice, problem-based learning and digital competencies as core mechanisms for pedagogical development.